2013
DOI: 10.1016/j.envpol.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Sediment pore water distribution coefficients of PCB congeners in enriched black carbon sediment

Abstract: More than 2300 sediment pore water distribution coefficients (KPCBi ds) of 93 polychlorinated biphenyls (PCBs) were measured and modeled from sediments from Indiana Harbor and Ship Canal. KPCBi ds were calculated from previously reported bulk sediment values and newly analyzed pore water. PCBs in pore waters were measured using SPME PDMS-fiber and ∑PCB ranged from 41 to 1500 ng L−1. The resulting KPCBi ds were ~ 1 log unit lower in comparison to other reported values. A simple model for the KPCBi d consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…These included polystyrene beads, PDMS fiber and a low-density polyethylene (LDPE) film, many of which have been used in research and development of passive sampling materials, albeit mostly for hydrophobic compounds. 4, 5, 28 Results showed that no uptake on LDPE was observed for either analyte, while PS beads and PDMS fibers produced aniline K ENM-W values that were at least 75% smaller than those measured for the best ENMs (Figure S5). Uptake of nitrobenzene was not measurable over our standard experimental timescale for any of the commercial materials, further highlighting the dearth of passive sampling materials currently available for some polar analytes outside of POCIS.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…These included polystyrene beads, PDMS fiber and a low-density polyethylene (LDPE) film, many of which have been used in research and development of passive sampling materials, albeit mostly for hydrophobic compounds. 4, 5, 28 Results showed that no uptake on LDPE was observed for either analyte, while PS beads and PDMS fibers produced aniline K ENM-W values that were at least 75% smaller than those measured for the best ENMs (Figure S5). Uptake of nitrobenzene was not measurable over our standard experimental timescale for any of the commercial materials, further highlighting the dearth of passive sampling materials currently available for some polar analytes outside of POCIS.…”
Section: Resultsmentioning
confidence: 94%
“…Further, these individual PCB concentrations are within the range and follow the same trend among congeners for published sediment pore water concentrations for the same IHSC sediment but using PDMS fiber (range from 0.4 to 60 ng L −1 ). 4 Further, PMMA and PS proved to be more sensitive than PDMS fiber; while it was possible to detect PCBs 206 and 209 on ENMs, these congeners were not amenable to analysis via PDMS fiber.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The more highly chlorinated PCB congeners are likely strongly sorbed to sediment organic carbon. Measuring PCB congeners profiles in sediment pore water (Liang et al 2014; Martinez et al 2013) would yield improved insights concerning biodegradation of soluble and bio-available PCB congeners.…”
Section: Discussionmentioning
confidence: 99%